Experimento do uso de jogos didáticos em logística no Novo Ensino Médio de Partintins - Araújo, Jucymara Soares (Brasil, 2024)
The New Secondary Education – NEM (law no. 13,415/2017) is a federal government program aimed at basic education that proposes a new curricular model for public and private schools in the 1st, 2nd and 3rd years of high school. . The new law is already a reality in many Brazilian schools that need to gradually adapt to the trends of the new legislation, following a programmatic implementation schedule defined by the Ministry of Education (MEC). The NEM has been a novelty in the school life of each student, especially those who have never had contact with the concepts of Administration, considering that basic education is limited to the teaching of classical subjects for the student's training. Therefore, learning in logistics needs to be differentiated, as it covers Administration concepts in a technical and scientific way, while still arousing interest on the part of students. In this context, the work problematizes the following question: How can an experiment with New High School students aiming to encourage creativity and collaboration through the creation of educational games? Its objective is to understand how the development of educational games stimulates the creativity and teamwork of students on the technical course in logistics, within the new high school. Carrying out this work is justified by the curiosity to know the logistics students' view of administrative science in its initial phase of training, since the age range of young high school students is between 15 and 18 years old. Methodologically, it is classified as applied research, with a qualitative approach, with the technique of direct observation, a camera was used as a resource to record activities and content analysis techniques. It was observed that students demonstrated positive engagement when collaborating as a team and using available financial resources to achieve the objective effectively. They managed to build the games, applying the logistical knowledge acquired in the classroom, respecting the pedagogical project of the discipline. In many cases, the students themselves became integral elements of the game, considered indispensable parts for its full functioning, contributing significantly to the outcome of the research.